رأس المال الاجتماعي - زاوي مريم; قادم جميلة (University of Eloued جامعة الوادي, 2024)
ملخص: نعالج في هذه الورقة البحثية انتقال مفهوم رأس المال الاجتماعي الترابطي والتجسيري -كشكلين هامين من أشكال راس المال الاجتماعي – من السياق الواقعي إلى سياق المجتمع الافتراضي ونناقش أيضا كيفية قراءة هذه المفاهيم وتطبيقها في بيئة الانترنت وهذا انطلاقا مما قدمه الباحث الأمريكي روبرت بوتنام باعتباره أول من طرح هذين المفهومين في سياق بحثه عن تراجع العلاقات الاجتماعية في المجتمع الأمريكي وما توفره من إطار هام لفهم العلاقة بين الفرد والمجتمع ودور كل منهما في تشكيل رأس المال الاجتماعي. خلصت الدراسة إلى عدد من النتائج والتوصيات أهمها أنه على الرغم من وجود بعض التشابه في كيفية تشكل كلا النوعين من رأس المال الاجتماعي بين السياق الواقعي والافتراضي إلا أنها تختلف في طبيعة وقوة الروابط المتشكلة واختلاف البنية المكونة لشبكة علاقات الأفراد، كما توصي الدراسة بضرورة تطوير مقاييس تتناسب مع التطورات المتسارعة في تكنولوجيات الاتصال من أجل فهم أفضل للتفاعلات الاجتماعية الافتراضية. الكلمات المفتاحية: رأس المال الاجتماعي، الرأس المال الاجتماعي الافتراضي الترابط، التجسير، المجتمع الافتراضي. Abstract: The present paper aims to highlight the transfer of the concept of social capital, both bonding and bridging, from the real context to the virtual community context. We also discuss how to interpret and apply these concepts in the online environment, building upon the work of American researcher Robert Putnam, who first introduced these concepts in his study on the decline of social relations in American society. This provides a valuable framework for understanding the relationship between individuals and society and the role of each in shaping social capital. Therefore, we shed light on the attempt to uncover how these concepts form in the virtual community environment. The study concludes with several results and recommendations, including the recognition that while there are similarities in the formation of both types of social capital between the real and virtual contexts, they differ in the nature and strength of the formed connections and the structural composition of individuals' relationship networks. The study recommends the need to develop measures that align with the rapid advancements in communication technologies to gain a better understanding of virtual social interactions.
قراءة تحليلية لمفهومي رأس المال الاجتماعي الترابطي والتجسيري في المجتمع الافتراضي
Keywords: رأس المال الاجتماعي; رأس المال الاجتماعي الافتراضي; الترابط; التجسير; المجتمع الافتراضي; social capital; virtual social capital; bonding; bridging; virtual community